CHALLENGES, EXPECTATIONS AND REALITY: THE ADAPTATION OF A GEOGRAPHY DEGREE TO THE EUROPEAN HIGHER EDUCATION ARE - Mireia BAYLINA; Maria VILLANUEVA (European Journal of Geography)
After the Sorbonne Declaration, the idea of a European Higher Education Area was launched, and universities have been pushed into a restructuring process with a strong emphasis on quality and excellence. In Spain, the focus on graduate employability impelled academics and professionals towards the formulation of a White Book on the state and the future of Geography in Higher Education (2004). This has been a useful tool concerning the general debate on the design of new university degrees within European regulations. This was the case at the department of Geography at the Autonomous University of Barcelona (UAB), where a three-year pilot program was undertaken, aiming to test the Bologna system before setting up and validating the new degrees. The outcomes of the White Book and of the pilot experience, proved to be very useful. The academic year 2009-10 began with a new Bachelors degree course in Geography and Regional Planning, a Spanish adaptation to European (Bologna) regulations. Although the short time that has elapsed since then makes it difficult to undertake a full evaluation of the process and reflect on its outcomes and impacts, the whole issue of reform is raising controversy leading to the reluctance to initiate further change, due mainly to the lack of internal debate about the process of change that apparently seems to be a response to global economic demands rather than academic ones. This paper analyzes the impact of the process in Spain, and specifically, in the Geography degree at UAB.